Building Information Modeling (BIM) In Effective Management of Development Projects and In the Administration of Housing Companies - Daniela SPIRKOVA; Petr STEPANEK (Communications of International Proceedings, 2023)
Building Information Modeling (BIM) can be described as a revolutionary process that has rapidly changed the way buildings are designed, constructed and operated (Hardin, 2009). Over the past few years, the term BIM has changed from a buzzword to the centerpiece of the Architecture-Engineering-Construction industry technology. Several benefits can be seen in the preparation of development projects as well as in the execution of construction. The BIM model forces the members of the implementation teams to first agree on a form of collaboration and only then start it. The benefit of using BIM for the investor is a higher quality of construction and at the same time a lot of important information about the realized object. The importance of BIM in building management lies primarily in the linking of the software with the BIM model, which makes it possible to work directly with real objects. The aim of this paper is to highlight the benefits of BIM technology in the design, construction industry and consequently in the property management by housing companies.
Keywords: Building Information Modeling; Effective management; Administration of housing companies